Malic enzyme 1 is a potential marker of combined hepatocellular cholangiocarcinoma, subtype with stem‐cell features, intermediate‐cell type. Issue 9 (18th June 2019) - Mihara, Yutaro; Akiba, Jun; Ogasawara, Sachiko; Kondo, Reiichiro; Fukushima, Hiroto; Itadani, Hiraku; Obara, Hitoshi; Kakuma, Tatsuyuki; Kusano, Hironori; Naito, Yoshiki; Okuda, Koji; Nakashima, Osamu; et al.
Abstract : Aim: Combined hepatocellular cholangiocarcinoma, subtype with stem‐cell features, intermediate‐cell subtype (INT) shows various histological appearances and could be misdiagnosed as intrahepatic cholangiocarcinoma (iCCA). In the present study, we aimed to identify specific histological diagnostic markers of INT. Methods: We extracted RNA from FFPE sections of six INT, five iCCA, and five hepatocellular carcinoma (HCC) cases and compared gene expression between INT, iCCA, and HCC by microarray analysis. We then undertook immunohistochemical (IHC) staining of potential key molecules identified by microarray analysis, the conventional hepatocytic marker, hepatocyte paraffin (HepPar)‐1, and the cholangiocytic markers, keratin (K) 7 and K19, on 35 INT, 25 iCCA, and 60 HCC cases. Results: Microarray analysis suggested that malic enzyme 1 (ME1) was significantly upregulated in INT. Immunohistochemical analysis revealed that the positive rates of ME1 in INT, iCCA, and HCC were 77.1% (27/35), 28.0% (7/25), and 61.7% (37/60), respectively. Analysis of classification and regression trees based on IHC scores indicated that HepPar‐1 could be a good candidate for discriminating HCC from the others with high sensitivity (93.3%) and high specificity (96.7%). A multiple logistic regression model and receiver operating characteristic curve analysis based on the IHC scores of ME1, K7, and K19 generated a composite score that can discriminate between INT and iCCA. Using this composite score, INT could be discriminated from iCCA with high sensitivity (88.6%) and high specificity (88.0%). Conclusions: We propose that ME1 is a useful diagnostic marker of INT when used in combination with other hepatocytic and cholangiocytic markers.